Good Job, Bad Job, No Job? Ethnicity and Employment Quality for Men in the UK - Ken Clark; Nico Ochmann (Institute of Labor Economics (IZA), 2022)
Ethnic minority men find it harder to obtain good jobs in the UK labour market than White British men. Over time, while the very high unemployment rates experienced by some non-white ethnic groups have significantly declined and their share of good jobs has grown, their share of bad jobs has grown by more. Bad jobs have replaced no jobs for these groups with Pakistani, Bangladeshi, Black Caribbean, and Black African men doing worst. In economic downturns access to good jobs gets relatively harder for some non-white ethnic minority groups compared to the White British majority. The second (UK-born) generation fares better in access to good jobs compared to their foreign-born counterparts. In particular second-generation Bangladeshis and Black Africans experience a higher probability of being in good jobs than the previous generation.
Keywords: J62; J71; J81; 330; ethnic groups; job quality; business cycles; labour markets